If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3 = 8x + -7 Reorder the terms: 3 + 7x = 8x + -7 Reorder the terms: 3 + 7x = -7 + 8x Solving 3 + 7x = -7 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 3 + 7x + -8x = -7 + 8x + -8x Combine like terms: 7x + -8x = -1x 3 + -1x = -7 + 8x + -8x Combine like terms: 8x + -8x = 0 3 + -1x = -7 + 0 3 + -1x = -7 Add '-3' to each side of the equation. 3 + -3 + -1x = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = -7 + -3 -1x = -7 + -3 Combine like terms: -7 + -3 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| 8x+6=20x+30+5x | | 20x+1=121 | | x+8=0.5 | | 2x+16=3(x-9) | | -10p+9p=-1 | | h^2-12h+35=0 | | 16x-64=9x+1 | | e^4x-3=6 | | 2(3x-1)=4(x-6) | | 3x+5=8x+16+2x | | 9m-2=-42+4m | | 6n-8=32+n | | 1.1(x+3)=66 | | m^2-43m+42=0 | | 3x-15=x-1 | | x^2-20+36=0 | | 0.02(5x+10)=6 | | 4(2x-3)=3x+8 | | 0.40x=12 | | d^2-19d+88=0 | | 0.4-0.7=0.22 | | -71=-4(b+8)-6(1+6b) | | 7x+3.9=6x+3.1 | | c^2+15+50=0 | | 0.06-x=1 | | -2x^2-8x-15=0 | | x^2+16+48=0 | | h^2+18h+45=0 | | 8x^2+1=-7x | | 3x-5=2(5-x) | | 4(x+9)=2(x+3) | | 8x^2=-64x |